Population abundance, structure and movements of the European pond turtle, Emys orbicularis (Linnaeus 1758) based on capture-recapture data in a Venice Lagoon wetland area, Italy. Issue 6 (2nd November 2021) - Liuzzo, Mirko; Borella, Stefano; Ottonello, Dario; Arizza, Vincenzo; Malavasi, Stefano
Abstract : A freshwater turtle monitoring programme along the inland margins of the Venice lagoon was initiated in 2019 in collaboration with the World Wild Fund for Nature (WWF-Italy). From a total of 336 European pond turtles ( Emys orbicularis ) captured and marked, 97 freshwater turtles were recaptured at least once (28.9% return rate) providing important information on population size, structure and movements of mature individuals within the study area. The population size was estimated with capture-recapture method (Capture-Mark-Recapture-CMR) at 1009.4 ± 365.2 pond turtles, with a mean density of 252.3 ± 91.3 ind./ha. The analysis of the movements showed that the average distance covered intra-water bodies was: 146.79 ± 117.08 m for females and 125.43 ± 112.34 m for males. A total of 17 E. orbicularis (eight females and nine males) out of 97 turtles changed the water body during the study period from April to early September. Only a female freshwater turtle migrated in all three study sites, being recaptured 1502.32 m from the tagging site. The percentage of captures was significantly higher in two canals than in the brackish lake habitat. Further research should address spatial distribution at a finer scale to evaluate the preferential habitat for threatened E. orbicularis populations in a transitional water system as the lagoon.